Study about the development of the temporomandibular joint in the human fetuses - Alves, Nilton [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
The temporomandibular joint (TMJ) is a highly specialized articulation that differs from all the other synovial articulations for many reasons. In children, different from what we observe in adults, these articulations have rarely been studied under the morphofunctional aspect, mainly in the embryonary and fetal stages. In this study 10 fetuses with ages varying from 16 to 39 weeks of intrauterine life were used, and it could be observed that the fibers and thickness of the articular disc, as well as the articular capsule and the condylar process, suffer modifications according to age. It was also observed that the superior head of the lateral pterygoid muscle inserts itself in the articular disc and capsule in all the ages studied. Also, the maturation, of the articular tissues, especially of the articular disc, as well as, the associated muscles, suggests that the TMJ was able to carry out mandibular movements since the 24th week of intrauterine life.
Keywords: Embryonary development; Fetal development; Temporomandibular joint